2017
DOI: 10.1002/2017gl075839
|View full text |Cite
|
Sign up to set email alerts
|

Seafloor Displacement After the 2011 Tohoku‐oki Earthquake in the Northern Japan Trench Examined by Repeated Bathymetric Surveys

Abstract: We conducted multibeam bathymetric surveys crossing the northern Japan Trench offshore Sanriku and examined seafloor displacement by means of the difference in bathymetry before and after the 11 March 2011 Tohoku‐oki earthquake. The seafloor displacements were less than several meters in vertical displacement and less than 20 m in trench‐normal horizontal displacement; consequently, lower amplitude seafloor displacements were evaluated. Comparatively, the landward lower slope near the trench was uplifted, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
45
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 16 publications
10
45
1
1
Order By: Relevance
“…Several methods have been developed to measure seafloor motion, including the following: Bottom pressure (e.g., Chadwick et al, ; Chierici et al, ) GPS acoustic (e.g., Chadwell & Spiess, ; Sato et al, ; Spiess, ; Spiess et al, ; Yokota et al, ) Direct‐path acoustic ranging (e.g., Chadwick & Stapp, ; Osada et al, ; McGuire & Collins, ) Multibeam sonar surveying (e.g., DeSanto et al, ; Fujiwara et al, ) Strainmeter and tiltmeter systems (e.g., Anderson et al, ; Zumberge et al, ) …”
Section: Discussionmentioning
confidence: 99%
“…Several methods have been developed to measure seafloor motion, including the following: Bottom pressure (e.g., Chadwick et al, ; Chierici et al, ) GPS acoustic (e.g., Chadwell & Spiess, ; Sato et al, ; Spiess, ; Spiess et al, ; Yokota et al, ) Direct‐path acoustic ranging (e.g., Chadwick & Stapp, ; Osada et al, ; McGuire & Collins, ) Multibeam sonar surveying (e.g., DeSanto et al, ; Fujiwara et al, ) Strainmeter and tiltmeter systems (e.g., Anderson et al, ; Zumberge et al, ) …”
Section: Discussionmentioning
confidence: 99%
“…We acquired high-resolution bathymetry data along the entire trench axis during the R/V Sonne SO251-1 cruise in October 2016 (Fujiwara et al, 2017;Strasser et al, 2017;Kioka et al, 2019). The data were acquired by a 12 kHz frequency KONGSBERG EM122 system equipped on R/V Sonne, which has 432 beams with a transducer of 0.5 (transmission) by 1 (receiving) degrees, and a dual swath (multiping) function.…”
Section: Bathymetry Datamentioning
confidence: 99%
“…We combined a modern digital evaluation model (DEM) calculated from bathymetry data at the water depths of <∼6,000 m acquired before 2011 by the Japanese research cruises (Hydrographic and Oceanographic Department Japan Coast Guard and JAMSTEC, 2011) with our post 2011 earthquake data (>5500 m depth) acquired during the R/V Sonne SO251-1 cruise (Fujiwara et al, 2017;Strasser et al, 2017;Kioka et al, 2019). This allows analyzing the flow network of potential sediment pathways across the margin into the trench and estimating relative contribution of sediment volume that can be routed into individual terminal trench basins.…”
Section: Bathymetry Datamentioning
confidence: 99%
“…Another characteristic is a proposed tsunami source region at around 39°-40°N, to the north of the large shallow slip area identified by tsunami data analyses [4][5][6] . Seafloor geodetic observations 7 and estimates of seafloor displacement based on bathymetric datasets [8][9][10][11] are strong evidence with which to examine the propagation of fault slip towards the seafloor through the trench axis area. Research using differential bathymetry has shown that seafloor displacement during the Tohoku earthquake was > 50 m near the trench axis at 38°05′-38°35′N, where the large slip occurred during the Tohoku earthquake 8,9 , but was not significant outside of this area 10,11 (Fig.…”
mentioning
confidence: 99%